Pengaruh Anggaran Partisipatif dan Budget Emphasis terhadap Budgetary Slack dengan Self Esteem sebagai Variabel Moderasi pada Hotel Berbintang di Kabupaten Gianyar - Ni Komang Sumadi; I Putu Deddy Samtika Putra; Ni Wayan Dila Indayani (UNHI Press, 2020)
The purpose of this study is to find empirical evidence of the influence of budgetary participation and Budget Emphasis on Budgetary Slack with Self Esteem as a moderating variable. This research was conducted at 21 star hotels in the district of Gianyar registered with PHRI Bali, 2017. The population is 167 Department of Head. The method used in determining the sample is purposive sampling and 137 department heads were obtained as research samples. The techniques used to collect data are observation, interviews, questionnaires, and documentation. While the analysis technique used is Moderated Regression Analysis (MRA). Based on the results of the analysis found that Participatory Budgeting has a positive and significant effect on Budgetary Slack with a regression coefficient of 0.328 and a significance value of 0,000 <0.05. Budget Emphasis has a positive and significant effect on Budgetary Slack with a regression coefficient of 0.215 and a significance value of 0.006 <0.05. Self Esteem cannot weaken the relationship of Participative Budget with Budgetary Slack with the results of the calculation of the regression coefficient of -0.035 and the significance value of 0.635> 0.05. Self Esteem can weaken the relationship of Budget Emphasis with the Budgetary Slack with the results of the calculation of the regression coefficient of -0.189 and the significance value of 0.011 < 0.05. This shows that the higher the Participatory Budget and Budget Emphasis, the higher the level of Budgetary Slack and the existence of a high Self Esteem will weaken the relationship between Budget Emphasis and Budgetary Slack, but Self Esteem cannot affect the relationship between Participative Budget and Budgetary Slack .